Media and sport: representations of coaches in a newspaper - Ferreira, Heidi Jancer [UNESP]; Metzner, Andreia Cristina [UNESP]; Ferreira, Janaína da Silva [UNESP]; Cunha, Luiza Darido Da [UNESP]; Pinto, Arthur Sales [UNESP]; Murbach, Marina Aggio [UNESP]; Drigo, Alexandre Janotta [UNESP] (FapUNIFESP (SciELO), 2018)
The study sought to identify and analyse the content related to sports and coaches in the print media. The analysis material was composed of 41 sports columns, published by large national newspaper for a month. The data were analysed by content analysis. It was found that the predominant theme was the male football big clubs and that 24 of the 41 speakers presented content on coaches. It was found that the speeches had an evaluative content of the work of coaches, contributing to the formation of opinion about the competence or incompetence of professionals and to build a representation of them to the public.
Mídia e esporte: representações sobre treinadores em um jornal impresso
Keywords: Media; Newspaper article; Physical education and training; Sports